2014
DOI: 10.1093/jnci/djt460
|View full text |Cite
|
Sign up to set email alerts
|

Early Impact of Human Papillomavirus Vaccination on Cervical Neoplasia--Nationwide Follow-up of Young Danish Women

Abstract: Six years after licensure of the quadrivalent HPV vaccine in Denmark, a reduced risk of cervical lesions is observed at the population level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
130
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(135 citation statements)
references
References 26 publications
2
130
1
1
Order By: Relevance
“…A study in Australia (Crowe et al 2014) showed a 43% decrease of atypical cells and a 62% decrease of HSIL in women aged 22-25 years with three vaccinations (after a lapse of 7 years). Similarly, a report in Denmark (Baldur-Felskov et al 2014) on uterine cervical cancer screening for women aged 20-21 years showed that atypical cells, CIN2 and CIN3 decreased by about 60%, 73%, and 80%, respectively. A study in Scotland (Pollock et al 2014) also showed that CIN3 decreased by about 55% after vaccination.…”
Section: Discussionmentioning
confidence: 81%
“…A study in Australia (Crowe et al 2014) showed a 43% decrease of atypical cells and a 62% decrease of HSIL in women aged 22-25 years with three vaccinations (after a lapse of 7 years). Similarly, a report in Denmark (Baldur-Felskov et al 2014) on uterine cervical cancer screening for women aged 20-21 years showed that atypical cells, CIN2 and CIN3 decreased by about 60%, 73%, and 80%, respectively. A study in Scotland (Pollock et al 2014) also showed that CIN3 decreased by about 55% after vaccination.…”
Section: Discussionmentioning
confidence: 81%
“…12 The quadrivalent HPV (6/11/16/18) virus-like particle (qHPV) vaccine is highly efficacious in preventing infection and cervical, vaginal, vulvar, and anal dysplasia caused by HPV 6/11/16/18 as well as HPV 6/11-related condyloma, [13][14][15][16] and the bivalent HPV (16/18) vaccine is highly efficacious against HPV 16/18-related infection and cervical dysplasia. 17 Postlicensure studies have shown a rapid decrease in the incidence of high-grade cervical abnormalities, [18][19][20][21] prevalence of vaccine HPV types, [22][23][24][25][26] and incidence of genital warts [27][28][29][30][31] in vaccinees. Data have shown that prophylactic HPV vaccination is generally safe and well tolerated.…”
Section: What This Study Addsmentioning
confidence: 99%
“…In addition, low vaccine coverage may jeopardize the expected public health benefits and cost-effectiveness of qHPV vaccine programs. As there are currently few studies on the real-world effects of the qHPV vaccine [17][18][19][20][21] and none on the population-level impact of qHPV vaccine programs on the burden of disease, we undertook a populationbased, retrospective cohort study to assess the impact of the qHPV vaccine and Ontario's qHPV vaccination program on the incidence of cervical dysplasia and AGW among adolescent girls.…”
Section: What This Study Addsmentioning
confidence: 99%